Moderating role of internal control between the gender diversity and board of director for financial performance of state-owned enterprises in China - Zhou, Jing; Ong, Tze San; Mohd Ashhari, Zariyawati; Mohammed Shah, Sabarina; Wen, Zhong (Human Resource Management Academic Research Society, 2023)
The issue of women goes out of their families to work in enterprises and gradually become senior managers is becoming more and more common. In this context, first, this study focuses on studying the role of the gender diversity and board of director for corporate financial performance. Second, this study considers the importance of internal control for corporate financial performance as a moderating factor between gender diversity and corporate financial performance. Third, this study highlights the significance of internal control for improving corporate financial performance. Lastly, this study uses the role of internal control as a moderating factor in the association between board of director and corporate financial performance. This study uses panel data of 814 A-share listed companies (8140 observations) in China from 2012 to 2021 and employs different dynamic panel regression models and robustness test. This study concludes following: first, the gender diversity has significance for improving the corporate financial performance. Second, board of director helps to improve the corporate financial performance. Third, internal control helps to enhance the corporate financial performance. Fourth, internal control positively affects between gender diversity and corporate financial performance. Fifth, internal control is beneficial to the board of director and corporate financial performance. This study looking at the female director from the different perspective by relating it to the special situation in China in the corporate governance study. This study contributes to look at indirect effect of internal control in the relationship.